Diagnosis of familial hypercholesterolemia in children: cascade screening from theory to practice - L. F. Galimova; D. I. Sadykova; E. S. Slastnikova; N. E. Usova (Кардиоваскулярная терапия и профилактика)
Aim. To conduct a cascade screening and to assess its effectiveness in the diagnosis of familial hypercholesterolemia (FH) in children.Material and methods. The study was conducted from January 2017 to August 2018 on the basis of the City Clinical Hospital № 7 and the Children’s Republican Clinical Hospital (Kazan, the Republic of Tatarstan). It consisted of identifying index cases — primary patients with FH with further examination of first- and second-degree relatives <18 years old. In adults, the diagnosis was established according to Dutch Lipid Clinic Network (DLCN) criteria): FH was diagnosed with a score of ≥6. In children and adolescents <6 years of age, the Simon Broome Registry criteria were used.Results. During this period, 2542 case histories of patients with cardiovascular diseases were analyzed, of which 1220 people with a total cholesterol >5 mmol/L were selected. Next, a targeted screening was carried out aimed at the diagnosis of FH, as a result of which 61 index patients were identified. At the next stage, as a part of cascade screening, 87 first- and second-degree relatives <18 years old were examined. In 43 (49,4%) children, heterozygous HF was diagnosed, of which in 4 patients the disease was detected by re-examination after 1 year.Conclusion. Cascade screening is a necessary and effective method for the diagnosis of АР in first- and second-degree relatives <18 years old. All children of the index patients should be monitored or genetic testing necessary to rule out FH. Today, it is important to increase awareness among clinicians about the diagnosis of FH in adults and children.